The influence of principals’ digital leadership and teacher empowerment training on elementary school teachers’ self-efficacy - Hidayatul Hikmah; Mada Sutapa (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study examines the combined and individual influence of principals’ digital leadership and teacher empowerment training on the self-efficacy of elementary school teachers in Central Lombok Regency, Indonesia. Employing a quantitative ex post facto design, the research involved a purposive sample of 100 teachers who had participated in empowerment training. Data were collected through validated questionnaires and analyzed using multiple linear regression. The results indicate that: (1) principals’ digital leadership has a significant positive effect on teacher self-efficacy (p = 0.020, t = 2.359); (2) teacher empowerment training also exerts a significant positive effect (p = 0.000, t = 4.554); and (3) collectively, these two factors significantly contribute to teacher self-efficacy (p = 0.000, F = 22.066), explaining 31.3% (R² = 0.313) of its variance. These findings underscore the importance of developing school principals’ digital leadership competencies and implementing structured teacher empowerment programs as effective strategies to bolster teachers' belief in their professional capabilities. The study provides empirical evidence for educational policymakers and school administrators aiming to enhance teacher quality and instructional effectiveness in the digital era.